Efektivitas Penambahan Enzim Papain dan Bromelin Terhadap Peningkatan Rendemen dan Mutu Minyak Kelapa Virgin - Khomeini Abdullah (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2026)
Research intend to know the effect of the concentration and effectiveness of papain and bromelain enzymes to increase the yield and quality of virgin coconut oil (VCO). The main ingredients used were old coconuts, pure papain and bromelain enzymes of Fonde brand (Tristan Lab, Bogor), with an enzymatic VCO production method. Research design used a non-factorial completely randomized design (CRD), 5 enzyme concentrations each added into 100 grams of coconut cream, and 3 replications randomly. Data of yield, water content and FFA analyzed used one-way analysis of variance (ANOVA) and continued with the Duncan test. The results showed the addition of 2% papain enzyme obtained the highest VCO yield of 25.05%, water content of 0.10%, FFA of 0.12%, and the oil condition was normal. Meanwhile, the addition of 2% bromelain enzyme obtained the highest VCO yield of 24.34%, water content of 0.12%, ALB of 0.13%, and the oil condition was also normal. Then, the highest yield obtained compared to the general yield of VCO, 2% papain enzyme more effective to increase VCO yield by 83.50%, than 2% bromelain enzyme only effective to increase VCO yield by 81.13%.